The CRM Handbook : a Business Guide to Customer Relationship Management - Dyché, Jill (Information Technology Ser., 2001)
Praise for The CRM Handbook "Want to avoid being one of the estimated 70 percent of companies who have tried implementing standalone CRM systems and failed? Confused by what your IT suppliers are telling you about 'CRM'? Then you need to read this book! Jill provides acomprehensive, practical, and easy to understand view of CRM and shows you how to successfully implement an enterprise customer-focused solution."--Kevin Bubeck Director, North America Information Strategy, Coca-Cola "CRM could be viewed as the ERP of the 2000s. As such, there will be multiple winners and losers as the marketplace places some large and strategic bets on this technology. In any case, Jill Dyché has captured the importance of the concepts and value derived through CRM solutions. Those needs will evolve, of course, but companies will always need the basics that have been discussed." - Brian Berliner Co-founder & EVP, Product Development, Acies Networks "The CRM Handbook provides information for the business person who is trying to understand CRM and how it can effect his/her business. It goes beyond the hype of the acronym and dives into the real issues that a company needs to consider before implementing a CRM solution." - Joy Blake Scott Director, Marketing and Communications, Fastwater, LLP "I haven't read anything that has such a practical approach. I view the book as having multiple benefits. It gives a good definition of CRM functionality but also gives detailed guidance of how to approach CRM in your organization." - Francine Frazer Principal Consultant, Net Perceptions "Even better than defining CRM, Jill took on all of the hyperlanguage around CRM and clearly differentiated the various incarnations of CRM. It's also usefulto know what can go wrong and the potential affects of such missteps. Too few authors level with readers about pitfalls!" - Linda McHugh Director, Professional Services, Cygent Inc. "The guides based on the business tools that Jill uses with her own clients are fabulous." - Robin Neidorf President, Electric Muse/Clio's, Pen Research & Interpretation, Inc. "The language is easy to read and easy to understand. Terms were well explained so that someone with no prior CRM experience could easily understand the text." - Marcia Robinson President, e-Business Strategies "An excellent study into what defines today's best practices in the CRM industry." - Gareth Herschel Senior Research Analyst, Gartner Research "Jill writes very well. Her writing ...